Optimization of Traffic Lighting by the Kamsel Unit in the Framework of Preventing Traffic Accidents in the Jurisdiction of Batang Polres - Susilo, Bima Satria (Advances in Police Science Research Journal, 2024)
This writing is motivated by the high number of traffic accidents in Batang Regency. The Kamsel Satlantas Unit of the Batang Police has carried out Traffic Information activities in order to prevent traffic accidents from occurring, but traffic accidents still occur frequently. For this reason, the author is interested in researching why Traffic Information by the Kamsel Unit in order to prevent traffic accidents in the jurisdiction of the Batang Police is not optimal. The purpose of this writing is to describe the implementation of traffic information and organizational resources by Kanit Kamsel in order to prevent traffic accidents in the jurisdiction of the Batang Police. This writing uses qualitative methods and types of field research because it collects data or information directly by going directly to the field with data collection techniques namely observation, interviews and document studies. The validity and reliability of the author uses triangulation. This writing is analyzed using management theory by George Terry and the theory of organizational resources and the concept of community education, the concept of Traffic Information and the concept of traffic accidents. The findings of this writing are one, the implementation of Traffic Information by the Kamsel Unit has not been carried out properly in terms of planning and traffic information materials have not been made before implementation, the organization has not been carried out by AAP by Kanit Kamsel, the implementation has not been in accordance with the Chief of Police's Implementation Guidelines No. Pol: Juklak/05/V/2003 2003 dated 29 May 2003 concerning the guidelines for the implementation of traffic education and supervision, the evaluation at the end of the activity has not yet been carried out and secondly, the organizational resources in traffic information activities that are an obstacle are men (humans), namely The number of Kamsel Unit personnel is still lacking and some members have not implemented Dikbangspes/Dikjur. Based on the results of the writing, the authors provide advice to the Batang Polres Satlantas Kamsel Unit to collaborate with the University at the faculty of communication in Batang Regency to provide training and knowledge to Satlantas members and create a Dikmas Then Application.